Inflammatory cytokines shape a changing DNA methylome in monocytes mirroring disease activity in rheumatoid arthritis. Issue 11 (1st August 2019) - Rodríguez-Ubreva, Javier; de la Calle-Fabregat, Carlos; Li, Tianlu; Ciudad, Laura; Ballestar, Maria L; Català-Moll, Francesc; Morante-Palacios, Octavio; Garcia-Gomez, Antonio; Celis, Raquel; Humby, Frances; Nerviani, Alessandra; Martin, Javier; et al.
Abstract : Objective: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease that mainly targets joints. Monocytes and macrophages are critical in RA pathogenesis and contribute to inflammatory lesions. These extremely plastic cells respond to extracellular signals which cause epigenomic changes that define their pathogenic phenotype. Here, we interrogated how DNA methylation alterations in RA monocytes are determined by extracellular signals. Methods: High-throughput DNA methylation analyses of patients with RA and controls and in vitro cytokine stimulation were used to investigate the underlying mechanisms behind DNA methylation alterations in RA as well as their relationship with clinical parameters, including RA disease activity. Results: The DNA methylomes of peripheral blood monocytes displayed significant changes and increased variability in patients with RA with respect to healthy controls. Changes in the monocyte methylome correlate with DAS28, in which high-activity patients are divergent from healthy controls in contrast to remission patients whose methylome is virtually identical to healthy controls. Indeed, the notion of a changing monocyte methylome is supported after comparing the profiles of same individuals at different stages of activity. We show how these changes are mediated by an increase in disease activity-associated cytokines, such as tumour necrosis factor alpha and interferons, as they recapitulate the DNA methylation changes observed in patients in vitro. Conclusion: We demonstrate a direct link between RA disease activity and the monocyte methylome through the action of inflammation-associated cytokines. Finally, we have obtained a DNA methylation-based mathematical formula that predicts inflammation-mediated disease activity for RA and other chronic immune-mediated inflammatory diseases.